Gender differences in awareness of diabetes mellitus among the rural population - Kumar, Iyshwarya Udaya; Murthy, Jaya Prakash; Upadya, Ujwal; Venkatesh, Mahesh (Asian Journal of Medical Sciences, 2017)
Background: Diabetes Mellitus is a chronic disorder, which is becoming rapidly epidemic in India.There are many complications occur due to uncontrolled diabetes mellitus.The outcome of diabetes depends mainly on the patient’s self-management like health-related behavior, which is based on his or her knowledge. Awareness on diabetes mellitus is still a lacunae among the Indian population. Aims and Objective: To determine the knowledge regarding awareness of diabetes like the risk factors, symptoms, complications and the management among the males and females in rural population. Materials and Methods: It is a cross sectional study conducted at the tertiary care center in rural Bangalore. A structured questionnaire was used and 300 adults were assessed on their knowledge regarding the awareness of diabetes. Result: Out of 300 adults, 159 adults (53%) had a history of diabetes. There was no gender difference observed regarding the awareness, nor the education played a role. There was significant difference observed in knowledge of diabetes Mellitus among the diabetics with respect to renal complications (p <0.013), symptoms like blurring of vision (p < 0.043) and burning feet (p < 0.009). Conclusion: Both the diabetic and non-diabetic groups had very low awareness regarding diabetes and associated risk factors. Both Males and females awareness levels were poor. Proper Diabetic education programme will help in raising public awareness of the disease. Asian Journal of Medical Sciences Vol.8(2) 2017 44-49